The making of Nigeria as a sovereign state - a theoretical prognosis and analysis of a balanced federalism - Bassey, Antigha Okon, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2014)
This paper presents a critical analysis of federal balance in Nigeria from the introduction of the federal principle through the 1954 constitution to the present day. The paper shows that federal balance is distorted in Nigeria federalism due to the interplay of eco-centric, ethno-centric and theo-centric forces inherent in the Nigerian body polity . The paper depended on secondary data sourced from text and related archival materials. The analysis in the paper reveals that there exists a socio-structural imbalance in Nigerian federalism marked by the preponderance of the federal government over sub-national units and of some ethnic groups and regions over others. This imbalance or disequilibrium threatens the very essence of the Nigerian state and propels Nigeria towards potential disintegration. The paper recommends the invocation of a Natu-centric force as put forward in the Bassonian theory through the introduction of a domiciliary policy as the only way to attaining unity, integration and development in Nigeria which will result in a federal balance. The invocations of such a Natu-centric force through the introduction and implementation of a domiciliary policy as practiced in the United States of America is expected to ameliorate and eradicate other forces acting against the attainment of true federalism occasioned by a federal balance, which is one of the fundamental determinants of the future of Nigeria as a sovereign state.